Policy adjustment to improve Quality of Public Service in UgandaPolicy adjustment to improve Quality of Public Service in Uganda - Uganda Development Management Policy Forum (Uganda Management Institute, 2017)
The general public in Uganda continues to register dissatisfaction with the quality of services and professional conduct of public servants yet Uganda’s education system is globally appreciated and enrolment into the Ugandan civil service requires high academic and proffessional qualifications.